Advance care planning for older adults with advanced dementia living at old age homes- perspective of the surrogates - Faye Chan; Jenny Lee; Derek Lai; Connie Tong; Christopher Lum; Jean Woo (Archives of Gerontology and Geriatrics Plus)
Background: ACP can be useful for person-centered dementia care. Without awareness of patients’ care preferences, surrogates are uncomfortable in making decisions to forgo LST for people with advanced dementia (PWAD), which can impact their quality of life. From clinical experience, the ACP sign-up rate of surrogates was low. Understanding the characteristics of the surrogates who completed the ACP process with signing document may shed light on our understanding of facilitators and overcoming of ACP barriers. Aim: The study aims to explore the views of surrogates who signed the ACP forms to forgo LST for PWAD. This retrospective qualitative study involved 23 surrogates who signed the ACP forms to forgo LST for PWAD. The interviews were transcribed and coded using a thematic content analysis framework. Results: An overarching thematic arrangement of the process for ACP decision-making by surrogates of PWAD includes seven emerged themes: (1) Pragmatic arrangement, (2) Timing of ACP, (3) Meaning of suffering, (4) Emotional stress, (5) Family support, (6) ACP barriers and (7) Decision-making. The progression from trigger/initiation, through internal struggles and addressing ACP factors (enhancers and barriers) to decisionmaking as an outcome was moderated by the healthcare team. Conclusion: Lacking awareness of ACP and patients’ care values and preferences can impact the surrogates negatively in making proxy care decisions. Public education and capacity building training for care professionals on ACP are needed. The healthcare team need to facilitate PWD and their families early enough to involve PWD with appropriate palliative care support including effective communication.